The Role of the Trusmi Batik Home Industry in Improving the Community's Economy - Mochamad Noufaldi (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2021)
This research departs from the phenomenon in Trusmi Village, Plered District, Cirebon Regency, where most of the population works in the batik industry. The number of batik industries in Trusmi village is a shift in livelihoods in the community, and there are still many unemployed. The method used in this research is descriptive and gathers information from informants through in-depth interviews. The results showed that the condition of the community before working as batik craftsmen was that the majority worked as farmers and odd jobs. Then, after the batik industry, the community's economic situation experienced a significant increase. So far, the role of the Trusmi batik industry is in the form of job creation. so that the community members who previously worked as farmers and casual laborers switched professions to work in the batik industry.